Deformation behavior and interface microstructure evolution of Al/Mg/Al multilayer composite sheets during deep drawing. (15th July 2015) - Li, Chen; Chi, Chengzhong; Lin, Peng; Zhang, Hua; Liang, Wei
Graphical abstract: Highlights: Orthogonal experimental design enabled the optimization of deep drawing of Al/Mg/Al multilayer composite sheets. The composite sheets obtained the maximum limit drawing radio of 3.1 at 200 °C. The microstructure of the intermetallic compound layers showed less cracks during deep drawing at 200 °C both in rolling direction and transverse direction. Abstract: The Al(5052)/Mg(AZ31)/Al(5052) multilayer composite sheets were fabricated via accumulative roll-bonding process at elevated temperatures. The present study aims to investigate the formability of the composite sheets by deep drawing test and orthogonal experimental design. The deep drawing parameters such as punch temperature, punch speed and die curvature radius have been optimized to maximize the limit drawing radio of the composite sheets at temperatures ranging from 150 °C to 230 °C. The limit drawing radio of the composite sheets obviously increased with the forming temperature, and the maximum drawing radio of 3.1 was obtained at 200 °C. After forming at 150 °C and 200 °C, the microstructure evolution of the intermetallic compound layers, consisting of Al12 Mg17 and Al3 Mg2 layers at the interface at different regions of the drawn cup in rolling direction (RD) and transverse direction (TD), was investigated. At the bottom region which was considered as less deformation, the microstructure of the intermetallic compound layers showed almost no changes both at 150 °C and 200 °C. However, the Al/Mg/Al multilayer composite sheets showed more satisfactory bonding properties when drawing at 200 °C with less cracks appearing at the wall region and corner region of the drawn cup than that at 150 °C.